Regulation of Autophagy-Related Protein and Cell Differentiation by High Mobility Group Box 1 Protein in Adipocytes - Huanhuan Feng; Lili Yu; Guojun Zhang; Guoyan Liu; Can Yang; Hui Wang; Xiangfeng Song (Mediators of Inflammation)
High mobility group box 1 protein (HMGB1) is a molecule related to the development of inflammation. Autophagy is vital to maintain cellular homeostasis and protect against inflammation of adipocyte injury. Our recent work focused on the relationship of HMGB1 and autophagy in 3T3-L1 cells. In vivo experimental results showed that, compared with the normal-diet group, the high-fat diet mice displayed an increase in adipocyte size in the epididymal adipose tissues. The expression levels of HMGB1 and LC3II also increased in epididymal adipose tissues in high-fat diet group compared to the normal-diet mice. The in vitro results indicated that HMGB1 protein treatment increased LC3II formation in 3T3-L1 preadipocytes in contrast to that in the control group. Furthermore, LC3II formation was inhibited through HMGB1 knockdown by siRNA. Treatment with the HMGB1 protein enhanced LC3II expression after 2 and 4 days but decreased the expression after 8 and 10 days among various differentiation stages of adipocytes. By contrast, FABP4 expression decreased on the fourth day and increased on the eighth day. Hence, the HMGB1 protein modulated autophagy-related proteins and lipid-metabolism-related genes in adipocytes and could be a new target for treatment of obesity and related metabolic diseases.